Chemical, Structural and Thermal Analysis of PET Flakes induced by Electron Beam Irradiation - Ismail, Nor Batrisya; Harun, Mohd Hamzah; Zaharuddin, Izzuddin Mohamad; Othman, Norfazlinayati; Mohamed, Mahathir; Alias, Mohd Sofian; Rahman, Mohd Faizal Abd; Umar, Khairil Nor Kamal; Mudri, Nurul Huda; Halim, Khairul Azhar Abdul; Tajau, Rida; Ghazali, Rusdyana Natasa; Aminuddin, Siti Nur Eyisha Wafa Mohd (Balai Publikasi Indonesia, 2025)
This study presents a comprehensive chemical, structural, and thermal characterization of polyethylene terephthalate (PET) flakes subjected to electron beam irradiation at doses of 0, 40, and 120 kGy. Post-consumer PET bottle flakes were analyzed using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Thermogravimetric Analysis (TGA) to determine irradiation-induced modifications. FTIR results reveal noticeable variations in key functional groups, particularly in the ester (C=O and C–O) and aromatic regions, indicating chain scission, partial cross-linking, and oxidation with increasing radiation doses. XRD analysis shows a progressive reduction in peak intensity and an increase in peak broadening, signifying decreased crystallinity and enhanced amorphous character due to structural disorder. TGA measurements demonstrate improved thermal stability of irradiated PET, with major degradation shifting from 450 °C in the non-irradiated sample to 480 °C after irradiation, and a clearer two-stage degradation pattern associated with structural rearrangements. These findings confirm that electron beam irradiation induces significant yet controlled modifications on PET’s molecular structure, crystallinity, and thermal behavior. Such property alterations highlight the potential of electron beam treatment as an effective pre-processing approach to enhance the recyclability and performance of waste PET, contributing to more sustainable plastic waste management strategies